Addition of glucagon‐like peptide‐1 receptor agonist therapy to insulin in C‐peptide‐positive patients with type 1 diabetes. Issue 4 (8th January 2019) - Kuhadiya, Nitesh D.; Prohaska, Ben; Ghanim, Husam; Dandona, Paresh
Abstract : We aimed to test the hypothesis that addition of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) to insulin in C‐peptide‐positive patients with type 1 diabetes (T1D) will result in a reduction in glycated haemoglobin (HbA1c) with reduced insulin requirements and a rise in C‐peptide concentrations. We conducted a retrospective analysis of 11 normal‐weight patients with T1D consecutively treated with a GLP‐1RA in addition to insulin. Paired t tests were used to compare the changes in HbA1c, insulin doses, body weight, body mass index, and C‐peptide concentrations prior to and 12 ± 1 weeks after GLP‐1RA therapy. At the end of 12 ± 1 weeks of GLP‐1RA therapy, HbA1c fell from 10.74 ± 0.96% (95 ± 10.5 mmol/mol) to 7.4 ± 0.58% (58 ± 6.3mmol/mol) ( P < 0.01), body weight fell from 71 ± 2.0 to 69 ± 2 kg ( P = 0.06), and total insulin dose was reduced by 64% from 33 ± 6 to 11 ± 5 units ( P < 0.01). Five out of 10 patients did not require any insulin. C‐peptide concentrations increased significantly from 0.43 ± 0.09 ng/ml (0.14 ± 0.02 nmol/L) to 1.42 ± 0.42ng/ml (0.47 ± 0.13 nmol/L) ( P = 0.01). Addition of GLP‐1RA therapy to insulin in normal‐weight patients with T1D led to a reduction in HbA1c with reduced insulin requirements, a 3.5‐fold increase in C‐peptide concentrations and freedom from insulin therapy in 50% of patients who tolerated the GLP‐1RA therapy over a period of 12 ± 1 weeks.